2021
DOI: 10.1002/jsfa.11191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biological and chemical additives on microbial community, fermentation characteristics, aerobic stability, and in vitro gas production of SuMu No. 2 elephant grass

Abstract: BACKGROUND:The study was conducted to evaluate the effects of biological and chemical additives on microbial community, fermentation characteristics, aerobic stability, and in vitro gas production of SuMu No. 2 elephant grass.RESULTS: Aerobic bacteria and yeast were not affected on days 5 and 7 but were significantly (P < 0.224) reduced on days 14, 30, and 60, whereas lactic acid and lactic acid bacteria were significantly (P > 0.001) higher in all ensiling days within all treatment groups. During the ensiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These findings suggest that the rice straw pretreated by MA or MA + M could provide more nutrients that can be absorbed and utilized by ruminants (Hymes-Fecht and Casper, 2021 ) and also imply a positive impact on animal performance (Mpanza et al, 2020 ). A previous study has also shown that the L. plantrum additives can improve in vitro degradation of elephant grass (Shah et al, 2021 ), and the IVDMD and IVNDFD increased by 13.97 and 32.69%, respectively. Similar findings were reported in forage-sorghum silage that the additive LAB can improve the in vitro digestibility of oat silage (Kaewpila et al, 2021b ).…”
Section: Discussionmentioning
confidence: 79%
“…These findings suggest that the rice straw pretreated by MA or MA + M could provide more nutrients that can be absorbed and utilized by ruminants (Hymes-Fecht and Casper, 2021 ) and also imply a positive impact on animal performance (Mpanza et al, 2020 ). A previous study has also shown that the L. plantrum additives can improve in vitro degradation of elephant grass (Shah et al, 2021 ), and the IVDMD and IVNDFD increased by 13.97 and 32.69%, respectively. Similar findings were reported in forage-sorghum silage that the additive LAB can improve the in vitro digestibility of oat silage (Kaewpila et al, 2021b ).…”
Section: Discussionmentioning
confidence: 79%
“…Fermentation is one of the main methods used by the food industry to manipulate and grow various types of bacteria, yeasts and fungi ( 16 ). However, in recent years, fermentation has been applied in various fields such as the mass production of highly complex substances including insulin, alternative proteins and antibiotics ( 17 ). In addition, the chemical and biological diversity of the natural products produced by microbial fermentation can improve quality and promote the absorption rate of active substances in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Yeasts and filamentous mold were the main microorganisms involved in the aerobic deterioration process of silages (Santos et al 2013b). When selecting a potent LAB for silage production that LAB should have characteristics of rapid growth (high cell density at ensiled silages), higher production of lactic acid with a marginal level of acetic acid, potent inhibition of pathogens (bacteria, yeast, and toxic metabolite producing mold), rapid reduction in pH, increased aerobic stability and dry matter content (DM), and long-term preservation with rich nutrients (Carvalho et al 2021;Soundharrajan et al 2017;Shah et al 2021). Lactic acid bacteria.…”
Section: Microbial Composition Of Tmr Silagementioning
confidence: 99%